Business intelligence and analytics (BIA) usage in the banking industry sector: An application of the toe framework - Ashraf Bany Mohammad; Manaf Al-Okaily; Mohammad Al-Majali; Ra'ed Masa'deh (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study aims to examine the factors that influence business intelligence and analytics (BIA) usage in the banking sector. Based on a comprehensive literature review, a theoretical model was developed to explore the impact of three key factors on business intelligence and analytics adoption and usage in the banking sector, namely technological, organizational, and environmental factors. The study used the Statistical Package for the Social Sciences (SPSS) to analyze data collected from 120 employees of Jordan Arab bank. The results revealed the critical impact of not only the existence of data and technology infrastructure but also the importance and availability of management and human resources support and capabilities. This study suggests that, more importantly, successful planning for business intelligence and analytics should go beyond the technology aspects to gain the full benefits of such technology, especially in the banking sector. Yet, we argue that more research needs to be conducted, especially in the context of developing countries, to fully understand how banking sectors can successfully implement and utilize business intelligence and analytics.
Keywords: 650; banking-industry sector; business intelligence and analytics; information technology; intelligence systems; jordanian context; TOE